UPAYA KONSELOR DALAM MEMBIMBING BELAJAR SISWA DI SEKOLAH DASAR/MADRASAH IBTIDAIYAH - ahmad zaini (Elementary: Islamic Teacher Journal, 2016)
In the study, some students quickly understand what was described by teachers, some are slow to understand. Students who quickly understood what was presented by the teacher would not have a significant problem, otherwise the students are slow in understanding a lesson is certainly a problem for him, if allowed to drag on. Therefore, there must be help and guide him so that learning the right way so he would not miss the lessons of more friends. Here we need the help of various parties. In the context of the subject teachers and school counselors have a major role in helping and encouraging the students. Moreover, elementary school students / madrasah are incidentally still in a period of growth and development. Interest guidance related to learning including the development of attitudes and habits, especially in doing the task in developing the skills and the attitude of the teachers, as well as fosters the discipline of learning and training, either independently or in groups. The efforts to do is first, enrichment fix that form of teaching that is cure or correct any teaching that makes for the better, second, enrichment activities, is a form of service that is given to a student or students who are very fast in learning, third , increase motivation to learn, teachers and other school staff are obligated to help learners improve motivation to learn, fourth, and fifth increase learning skills, the development of attitudes and good study habits.